POLITENESS STRATEGIES REFLECTED IN THE GRAHAM NORTON SHOW ON BBC ONE - Yesi Purnamasari; Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2017)
The study construes the types of politeness strategies reflected in the show and the factors that might influence the choice of the strategies. The theory of politeness strategies as proposed by Brown & Levinson (1987) was applied in order to analyze the data. The results indicate that the show demonstrates the application of bald on record (8), positive politeness (181), negative politeness (14), and off record strategies (6). The factors that might influence the selection of the strategies are the payoffs, which means considering the advantages in gaining satisfaction and respect from the speakers. The circumstances deal with the distance, power and ranking of imposition. The distance between the speakers is low as they are friends, or at least they come from the same background - entertainment. The host has more power as he rules the conversations. The topic discussed was not a heavy topic, so the possibility of threatening other’s face might not be that significant.Key words: politeness strategies, talk show